KUALITAS PUPUK ORGANIK CAIR PLUS BERBAHAN DASAR PUTRI MALU (Mimosa pudica Linn.) YANG DIFERMENTASI DENGAN MENGGUNAKAN BEBERAPA JENIS BIOAKTIVATOR - Marisa Nopriyanti; Fadjar Rianto; Wasi'an Wasi'an (Partner, 2020)
Liquid Organic Fertilizer (LOF) is one type of fertilizer that is currently an alternative fertilizer that is widely used by the community. The purpose of this study was to evaluate the quality of liquid organic fertilizers made from the fermentation of the basic ingredients of the Mimosa pudica Linn. Using several types of bio activators.The study used a two-factorial completely randomized design (CRD). The treatment factors were the type of liquid fertilizer organic matter (A) and the microbial starter (B), there were 6 treatment combinations and was repeated 4 times with a three-day variable observed pH, temperature, color, and aroma descriptive organoleptic test. After becoming LOF, the content of N, P, K, C-Organic, Fe, and Pb were analyzed. The results of the analysis showed that the temperature and pH of the finished liquid fertilizer reached 29-31 ° C with a pH of 4. The K content in the liquid fertilizer was higher when using a mixture of canopy and root of the daughter of shame. The C-Organic content in liquid fertilizers is relatively the same. The color and aroma quality of all treatments were the same as well as the P. content. Fe and Pb content were classified as very low as required in liquid fertilizer products. Keywords: shy daughter Plants, Bio activators, Fermentation, LOF.